Consumption of Eryngium proteiflorum by the Mexican cottontail (Sylvilagus cunicularius) - Glebskiy, Yury; Parra-Campos, Daniela Aimee; Cano-Santana, Zenón (Therya Notes, 2024)
Despite its abundance and important role in ecosystems, the diet of the Mexican cottontail, Sylvilagus cunicularius, has not been studied enough. Previous studies report only the consumption of Poaceae species by this cottontail. In this note, we report the consumption of Eryngium proteiflorum by the Mexican cottontail at Pico del Águila located on top of the Ajusco volcano, México City, México. Cottontails consume E. proteiflorum leaves from the base to avoid spikes, and they use this source of food all year. Therefore, E. proteiflorum could be an important source of nutrition for cottontails, and they appear to be important consumers of this plant.